Nuclear Localization of Schizosaccharomyces pombe Mcm2/Cdc19p Requires MCM Complex Assembly - Pasion, Sally G. (The American Society for Cell Biology, 1999)
The minichromosome maintenance (MCM) proteins MCM2–MCM7 are conserved eukaryotic replication factors that assemble in a heterohexameric complex. In fission yeast, these proteins are nuclear throughout the cell cycle. In studying the mechanism that regulates assembly of the MCM complex, we analyzed the cis and trans elements required for nuclear localization of a single subunit, Mcm2p. Mutation of any single mcm gene leads to redistribution of wild-type MCM subunits to the cytoplasm, and this redistribution depends on an active nuclear export system. We identified the nuclear localization signal sequences of Mcm2p and showed that these are required for nuclear targeting of other MCM subunits. In turn, Mcm2p must associate with other MCM proteins for its proper localization; nuclear localization of MCM proteins thus requires assembly of MCM proteins in a complex. We suggest that coupling complex assembly to nuclear targeting and retention ensures that only intact heterohexameric MCM complexes remain nuclear.